A briefly overview of the research progress for the abscisic acid analogues - Liu, Yaming; Chen, Shunhong; Wei, Panpan; Guo, Shengxin; Wu, Jian (Frontiers in Chemistry, 2022)
Abscisic acid (ABA) is an important plant endogenous hormone that participates in the regulation of various physiological processes in plants, including the occurrence and development of somatic embryos, seed development and dormancy. ABA is called "plant stress resistance factor", while with the limitation of the rapid metabolic inactivation and photoisomerization inactivation of ABA for its large-scale use. For decades, hundreds of ABA analogues (similar in structure or function) have been synthesized to develop highly active plant growth regulators and tools to elucidate ABA perception. In this review, we summarize a variety of ABA analogues, especially the ABA receptor analogues, and explore the mechanisms of ABA action and catabolism, which will facilitate the development of novel ABA analogues with high biological activities.